ASSOCIATION BETWEEN HEMODIALYSIS ADEQUACY AND QUALITY OF LIFE IN CHRONIC RENAL PATIENTS UNDERGOING HEMODIALYSIS - Alfrina Hany; Linda Wieke Noviyanti; Endang Susilowati (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2019)
Hemodialysis adequacy describes a measure of the hemodialysis doses. Automatic measurement of adequacy through a hemodialysis machine has a more efficient advantage and can be accessed at any time. The purpose of this study was to determine the association between adequacy hemodialysis and the quality of life among chronic renal failure patientsundergoing hemodialysis. This study used a correlational analytic observational study with a cross sectional design. Data analysedwith the Spearman Rank correlation test. The subjects were 31 chronic renal failure patients undergoing hemodialysis, determined by consecutive sampling method. Data were collected retrospectively through hemodialysis record and the KDQOL SF-36 questionnaire. The result was there was no significant relationship between the adequacy of hemodialysis and quality of life in all dimensions of quality of life except for the dimensions of the physical composite (p=0,013, Î±=0,05) r=-0,449. There was a relationship between length of time undergoing hemodialysis and physical composite (p= 0,046, Î±=0,05), r = -0,367. The conclusion is confirmation of adequacy with blood urea examination is necessary.Monitoring machine monitor curves for smooth access, Qb, duration of hemodialysis and recirculation during hemodialysis is important to support the achievement of the expected adequacy. Evaluating the quality of life of patients needs to be done regularly.